The Roles of Supervisor Care and Trust and Sense of Belonging in Promoting Internship Satisfaction - Melinda K. Adams; Jody E. Jessup-Anger (Teaching & Learning Inquiry: The ISSOTL Journal)
This study examines how relational aspects of the internship experience, namely students’ perceptions of a supervisor’s care and trust and students’ sense of belonging, factor into students’ satisfaction with their internship experience. We found that relational aspects impacted internship satisfaction. Although students’ perceptions of a supervisor’s care and trust were not a significant predictor of satisfaction, their sense of belonging was significant. Further analysis pointed to opportunities to use career related skills and gain confidence to pursue future job opportunities as significant in building students’ sense of belonging.